Investor protection and foreign stakeholders - Maela Giofré (Center for Economic Studies and ifo Institute (CESifo), 2010)
Different investor classes are endowed with different rights, and conflicting interests among them can make protections afforded to one party detrimental to another. Indeed, we find that investor protection laws have sizeable 'cross' effects on foreign portfolio investment and the direction of these effects supports the conjecture that foreign stakeholders are more sensitive to the perceived riskiness of assets than domestic investors. Specifically, we find that strong protection of creditor rights - limiting excessive risk taking - positively affects foreign shareholders, whereas strong protection of shareholder rights - potentially shifting firms toward riskier projects - negatively impacts foreign bondholders.
Keywords: G11; G15; G30; 330; international portfolio investments; investor protection; bondholders-shareholders conflicts; Portfolio-Investition; Anlegerschutz; Gläubigerschutz; Stakeholder; Schätzung; Industriestaaten